The Flow and Fracture of Cracked Ice: Experiments to Aid Modeling - Schulson, Erland M (1997)
The long-term goal is to understand and model the formation of oriented leads in sheets of first-year sea ice with the ultimate goal of contributing to the next generation sea ice model.